Overexpression of Mechano-Growth Factor Modulates Inflammatory Cytokine Expression and Macrophage Resolution in Skeletal Muscle Injury - Sun, Keng-Ting; Cheung, Kwok-Kuen; Au, Shannon W. N.; Yeung, Simon S.; Yeung, Ella W. (Frontiers in Physiology, 2018)
In muscle regeneration, infiltrating myeloid cells such as macrophages mediate muscle inflammation by releasing key soluble factors. One such factor, insulin-like growth factor 1 (IGF-1), suppresses inflammatory cytokine expression and mediates macrophage polarization to anti-inflammatory phenotype during muscle injury. Previously the IGF-1Ea isoform was shown to be anti-inflammatory. Another isoform of IGF 1, mechano-growth factor (MGF), is structurally and functionally distinct from IGF-1Ea, but its role in muscle inflammation has not yet been characterized. In this study, we hypothesized that MGF expression in muscle injury modulates muscle inflammation. We first investigated changes of transcription and expression of MGF in response to skeletal muscle injury induced by cardiotoxin (CTX) in vivo. At 1-2 d post injury, Mgf expression was significantly upregulated and positively correlated with that of inflammatory cytokines. Immunostaining revealed that infiltration of neutrophils and macrophages coincided with Mgf upregulation. Furthermore, infiltrating neutrophils and macrophages expressed Mgf, suggesting their contribution to MGF upregulation in muscle injury. Macrophages seem to be the predominant source of MGF in muscle injury, whereas neutrophil depletion did not affect muscle Mgf expression. Given the association of MGF and macrophages, we then studied whether MGF could affect macrophage infiltration and polarization. To test this, we overexpressed MGF in CTX-injured muscles and evaluated inflammatory marker expression, macrophage populations, and muscle regeneration outcomes. MGF overexpression delayed the resolution of macrophages, particularly the pro-inflammatory phenotype. This coincided with upregulation of inflammatory markers. Annexin V-based flow cytometry revealed that MGF overexpression likely delays macrophage resolution by limiting macrophage apoptosis. Although MGF overexpression did not obviously affect muscle regeneration outcomes, the findings are novel and provide insights on the physiological roles of MGF in muscle regeneration.